Neuroimaging of Vermiform Giant Arachnoid Granulations in Children - Oswaldo A. Guevara Tirado; Livja Mertiri; Stephen F. Kralik; Nilesh K. Desai; Thierry A. G. M. Huisman; Maarten H. Lequin; Huy (Brandon) (MDPI AG, 2024)
Arachnoid granulations (AGs) are generally benign structures within the subarachnoid space that extend into the dural sinuses and calvarial bone. They can present in a variety of sizes but are termed 'giant' arachnoid granulations (GAGs) when they are larger than 1 cm in diameter or take up a significant portion of the dural sinus' lumen. Vermiform giant arachnoid granulations are a specific type of GAG that are known for their worm-like appearance. Specifically, these vermiform GAGs can be challenging to diagnose as they can mimic other pathologies like dural sinus thrombosis, sinus cavernomas, or brain tumors. In this case series, we present two cases of vermiform giant arachnoid granulations, discuss their imaging characteristics and highlight the diagnostic challenges to improve identification and prevent misdiagnoses.